HUMAN FLOURISHING AS AN OUTCOME OF INTEGRATED PRIMARY CARE AND COMMUNITY BASED MODELS OF CARE. (11th November 2018) - Faul, A; D'Ambrosio, J; Yankeelov, P; Cotton, S; Furman, C; Hall-Faul, M; Gordon, B; Wright, R
Abstract: The objective of this study is the development and validation of the Flourish Index (FI), an instrument that can be used to evaluate integrated care. The Flourish Index was developed as part of the Human Resources & Services Administration (HRSA) Rural Geriatric Workforce Enhancement Program (GWEP) at a university in the Midwest. We evaluated the impact of the Flourish Model using the Flourish Index to measure improvement in optimal life functioning of rural older adults. The Flourish model uses community health navigators (CHNs) and community organizers (COs) to connect clinical and community care plans. One of the primary goals of the Flourish model is to help older adults flourish as they age irrespective of their chronic conditions or risks within each determinant of health. Categorical Principal Components Analysis (CATPCA) showed a five-dimensional structure with psychological determinants loading on the biological determinants of health. Internal consistency (Cronbach Alpha) for the determinants were as follows: biological/psychological = 0.73, individual = 0.58, environmental = 0.62, health services = 0.65, social determinants = 0.67, and total score = 0.97. Sensitivity to change was shown for the total FI score (F1, 22=8.82, p=0.01) and social (F1, 22=5.82, p=0.02); with a trend toward sensitivity for individual health behaviors (F1, 22=3.95, p=0.06) and health services (F1, 22=3.26, p=0.09). Preliminary analysis of the FI shows promise for the usability of the Index to provide insight into the fundamental challenges of aging. It brings greater clarity in caring for older adults and supports quality evaluation of integrated care coordination models.